2020
DOI: 10.1002/jbt.22592
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative effect and autophagy induction of curcumin derivative ZYX02‐Na on the human lung cancer cells A549

Abstract: At present, a large number of curcumin derivatives had been produced and identified aiming to replace the curcumin in view of its low bioavailability and stability. Here, a novel curcumin derivative ZYX02-Na was first used to reduce the cell viability of human non-small cell lung cells A549, which was confirmed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. Flow cytometry and Western blot analysis showed that ZYX02-Na could lead to cell cycle arrest in G0/G1 phase, which demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…In fact, in our previous studies, several Cur analogs, such as MOMI-1, ZYX01, and ZYX02-Na were shown to activate the autophagic process and lead to death of non-small lung cancer A549 cells. [22][23][24] In the present study, EF-24 exhibited similar cellular effect on MCF-7 cancer cells. As expected, fluorescent and electron microscopy observations detected the autophagic vacuoles and F I G U R E 4 Confocal microscopy analysis of the inhibition of autophagosome-lysosome fusion by EF-24.…”
Section: Discussionsupporting
confidence: 68%
“…In fact, in our previous studies, several Cur analogs, such as MOMI-1, ZYX01, and ZYX02-Na were shown to activate the autophagic process and lead to death of non-small lung cancer A549 cells. [22][23][24] In the present study, EF-24 exhibited similar cellular effect on MCF-7 cancer cells. As expected, fluorescent and electron microscopy observations detected the autophagic vacuoles and F I G U R E 4 Confocal microscopy analysis of the inhibition of autophagosome-lysosome fusion by EF-24.…”
Section: Discussionsupporting
confidence: 68%
“…In fact, our previous study demonstrated that curcumin analogs MOMI-1, ZYX01, and ZYX02-Na resulted in the autophagic cell death process of non-small lung cancer cells A549. [25][26][27] In this study, after EF-24 incubation, red autophagic vacuoles, typical autophagic double or multiple membrane structures, and increasing expression of LC3B-II in MDA-MB-231 cells could be detected, suggesting that EF-24 might trigger autophagy in MDA-MB-21 cells.…”
Section: Ef-24 Exerts An Inhibitory Effect Via the Ros-mediating Pathwaysupporting
confidence: 51%
“…In fact, our previous study demonstrated that curcumin analogs MOMI‐1, ZYX01, and ZYX02‐Na resulted in the autophagic cell death process of non‐small lung cancer cells A549. [ 25–27 ] In this study, after EF‐24 incubation, red autophagic vacuoles, typical autophagic double or multiple membrane structures, and increasing expression of LC3B‐II in MDA‐MB‐231 cells could be detected, suggesting that EF‐24 might trigger autophagy in MDA‐MB‐21 cells. EF‐24 could also bring about increase of LC3B‐II level in the presence of the late autophagy inhibitor CQ, confirming that EF‐24 indeed induced complete autophagy rather than blocked the degradation of autophagic vesicles.…”
Section: Discussionmentioning
confidence: 52%
“…Cleavage of Beclin-1 promotes the release of proapoptotic factors from the mitochondria which in turn activate caspases that cleave PARP, thereby triggering apoptosis [50]. Other studies have found anticancer effects of various naturally-derived compounds that were associated with AMPK activation in NSCLC [51][52][53]. Treatment of lung cancer cells (HOP62 and H1975) with the polyphenol ellagic acid resulted in AMPK activation and reduced cell proliferation [51].…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of ellagic acid reduced the growth of Lewis Lung Carcinoma (LLC) xenografts in mice and was associated with increased levels of phosphorylated AMPK and ACC in tumour tissues [51]. Treatment of A549 NSCLC cells with a synthetic derivative of the polyphenol curcumin inhibited proliferation and migration, and these effects were associated with increased phosphorylation/activation of AMPK [52]. The natural compound phillygenin from the medicinal herb Forsythia suspensa, activated AMPK, inhibited growth, and promoted apoptosis of A549 and SPC-A1 NSCLC cells in vitro and administration of phillygenin to A549 xenografted nude mice resulted in reduced tumour volume [53].…”
Section: Discussionmentioning
confidence: 99%